A Systematic Approach to Requirements Engineering Process Improvement in Small and Medium Enterprises: An Exploratory Study - Kabaale, Edward; Nabukenya, Josephine (Springer, Berlin, Heidelberg., 2011)
Requirements Engineering (RE) studies have demonstrated that requirements errors affect the quality of software developed, making software requirements critical determinants of software quality. Requirements Engineering Process Improvement (REPI) models have been provided by different authors to improve the RE process. However, little success has been achieved in Small and Medium Enterprises (SMEs) software companies especially in transitional countries such as Uganda. This study reports on an exploratory study which provides insights into current RE practices in four Ugandan SME software companies, critical success factors and challenges that impede REPI. As a result a Systematic Approach to REPI has been designed following the design science approach. It provides guidelines and steps for SMEs in improving their RE processes.
Keywords: Requirements Engineering, Process Improvement, Software Process Improvement